Distinctive features of bovine alphaherpesvirus types 1 and 5 and the virus-host interactions that might influence clinical outcomes - Marin, Maia Solange (2019)
Bovine herpesvirus types 1 (BoHV-1) and 5 (BoHV-5) are two closely related alpha-herpesviruses. BoHV-1 causes several syndromes in cattle, including respiratory disease and sporadic cases of encephalitis, whereas BoHV-5 is responsible for meningoencephalitis in calves. Although both viruses are neurotropic they differ in their neuropathogenic potential. This review summarizes the findings on the specific mechanisms and pathways known to modulate the pathogenesis of BoHV-1 and BoHV-5, particularly in relation with respiratory and neurological syndromes, which characterize the infections by each virus, respectively.